2014
DOI: 10.1371/journal.pone.0106666
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Indoor Extremely Low Frequency and Low Frequency Electromagnetic Fields in the INMA-Granada Cohort

Abstract: ObjectiveTo characterize the exposure to electric fields and magnetic fields of non-ionizing radiation in the electromagnetic spectrum (15 Hz to 100 kHz) in the dwellings of children from the Spanish Environment and Childhood-“INMA” population-based birth cohort.MethodologyThe study sample was drawn from the INMA-Granada cohort. Out of 300 boys participating in the 9–10 year follow-up, 123 families agreed to the exposure assessment at home and completed a specific ad hoc questionnaire gathering information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
0
17
3
1
Order By: Relevance
“…The recruitment and characteristics of the study population were previously reported [Calvente et al, , 2015]. Briefly, the study sample was drawn from the INMA cohort study, a population‐based study in seven regions of Spain, which aims to explore the role of environmental pollutants in air, water, and diet during pregnancy and early childhood in relation to child growth and development.…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment and characteristics of the study population were previously reported [Calvente et al, , 2015]. Briefly, the study sample was drawn from the INMA cohort study, a population‐based study in seven regions of Spain, which aims to explore the role of environmental pollutants in air, water, and diet during pregnancy and early childhood in relation to child growth and development.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the analysis showed that exposure to RF is correlated with cognitive processes, behaviour or memory and can cause pathological hazards. According to Calvente et al, children continuously exposed to radiofrequency radiation been consistent signs of health effects after exposure to levels below the ICNIRP limits [36].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, exposure to ELFs has generally been estimated by indirect methods such as those described by Wertheimer and Leeper [ 4 ]. However, studies are starting to emerge in which ELF exposure is estimated by spot and longer-term direct measurements, and taking into account all the potential sources of emission [ 33 ], while others use personal measurements [ 37 ]. With regards to RFs, the majority of studies published on the effects of RF exposure on health consider the use of mobile and cordless phones (900 MHz to 2600 MHz), with data mostly from questionnaires [ 6 8 , 38 ], not taking into account environmental sources of RF EMFs (mobile phone base stations, radio and TV transmitters, WiFi and cordless phone base stations), to which children are exposed on a daily basis, at school and/or at home.…”
Section: Discussionmentioning
confidence: 99%
“…For measuring narrow- and broadband ELF fields and broadband RF fields strength, a NBM-550 Broadband Field Meter basic unit was used in one of the study regions, with an EHP-50D Electric Field and Magnetic Field and Flux Density Isotropic Probe Analyser for fields of 5 Hz to 100 kHz and an EF 0691 Isotropic Probe for frequencies of 100 kHz to 6 GH, all from Narda Safety Test Solutions (Germany). In another study region, for broadband measurements at ELFs and RFs, a TS/001/UB Taoma Broadband Field Meter basic unit was used with TS/002/BLF and TS/003/ELF isotropic probes for analysing the magnetic and electric fields respectively, in the 15 Hz-100 kHz frequency range and a TS/004/EHF isotropic electric field probe for the 100 kHz to 6 GHz frequency range, all from Tecnoservizi (Rome, Italy) [ 32 , 33 ]. For measuring narrowband RF fields in the 87.5 MHz–6 GHz range, ExpoM-RF 3 personal portable exposimeter (Fields at work; Zurich, Switzerland) was used in all the regions of the Project.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation